EX ORIENTE PAX. A MONARCHIA KELETI FRONTI HÁBORÚJÁNAK VÉGE 1917-BEN - Dávid, Ligeti (Közép-Európai Közlemények, 2020)
In summer 1917, the last major campaign was fought between Russia and the Austro-Hungarian Empire. After the abolition of the Romanov dynasty in March 1917, the new Russian government decided that the Dual Monarchy had to be knocked out of the war. To execute this bold plan, the Russian Minister of War Alexander Fyodorovich Kerensky initiated a grand-scale offensive. Although initially achieving impressive successes, the Russians could not duplicate the results of the Brusilov Offensive of the previous year. After withstanding the attack, the Central Powers led a successful counteroffensive, which nearly swept the enemy completely out of Austro-Hungarian territory. This near-victory transformed into a catastrophe for the Russians, for they could not continue the war. After the Bolshevik takeover, they were forced to sign a ceasefire. In March 1918, a peace treaty was also signed in Brest-Litovsk, which sealed the defeat of Russia in WW1.